(untitled) (Heritage, 2025)
The paper deals with taboo as an inseparable feature of the visual arts throughout history, which often decisively determines the character of an individual epoch, culture or style. Selected examples from several creative periods, religions and civilizations show that breaking taboos is an integral part of the development process in art and the way art communicates with its environment-society in general, not just the part of the society that is interested in art. The presented examples of taboos relate both to the selection of themes and motifs, and to the creative process itself in its various phases. It also points to the development of awareness of the existence of taboos in conclusion with (post)modern art, where their negative evaluation and breaking have in a certain way become the obligations of creators.